How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Research Component. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Executive summary - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Rapport de synthèse - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Quand le terrain informe les interventions communautaires. - van Kemenade, Solange; Tremblay, Éléonore; Benhamadi, Bey; Moussard, Aline; Michel, Jean Nephetaly (Minorités linguistiques et société, 2024)
L’Abécédaire d’un cerveau en santé – Sensibilisation à la démence dans l’Ouest et le Nord est un projet chapeauté par RésoSanté Colombie-Britannique et mis en oeuvre en partenariat avec les réseaux de Santé en français de la Saskatchewan, de l’Alberta et du Yukon. Ses objectifs étaient : a) produire des connaissances pour mieux comprendre la problématique de la démence et son impact dans les communautés francophones dans les provinces et le territoire ciblés; b) prévenir la démence et réduire la stigmatisation des personnes atteintes de troubles neurodégénératifs. Cet article se concentre sur le volet recherche du projet qui a accompagné l’intervention communautaire. Des entrevues semi-structurées (N=29) et un sondage en ligne (N=282) auprès des communautés francophones, des personnes proches aidantes, des intervenantes et des intervenants ainsi que du personnel oeuvrant dans les organisations de la francophonie ont été réalisées. L’étude a contribué à documenter la nécessité de services de prévention, de diagnostic, de soutien et de soins en français en matière de troubles neurocognitifs, à repérer des populations plus vulnérables et à recenser des bonnes pratiques. La recherche sur le terrain a éclairé les responsables et les partenaires du projet dans le choix des interventions communautaires appropriées en matière de prévention et de sensibilisation dans un contexte linguistique minoritaire. Mots-clés : troubles cognitifs, démence, francophones en situation minoritaire, interventions communautaires, Canada